The Relationship Between Age, Stress Levels, Physical Activity, and Sleep Quality and The Incidence of Hypertension Among The Elderly - Latifah Oktafianti; Veni Fatmawati; Riska Risty Wardhani (Jurnal Sehat Indonesia (JUSINDO), 2026)
Hypertension is a condition of elevated blood pressure >140/90 mmHg, which is influenced by various factors. One non-modifiable factor is age, as increasing age leads to a decrease in blood vessel elasticity, which increases the risk of hypertension. Furthermore, modifiable factors such as low physical activity, stress levels, and poor sleep quality also play a role in increasing blood pressure. To determine the relationship between age, stress levels, physical activity, and sleep quality with the incidence of hypertension. This study is an observational study with a total sampling technique and uses the Spearman rank test. The sample in this study were elderly people at the Aisyiyah Pajangan Branch with a population of 120 elderly people and 71 elderly people suffered from hypertension. The variables in this study were age, stress level, physical activity and sleep quality as independent variables and hypertension as dependent. The measuring instruments used were the Perceived Stress Scale (PSS-10) for stress levels, the Physical Activity Scale for Elderly (PASE) for physical activity, the Pittsburgh Sleep Quality Index (PSQI) for sleep quality and a sphygmomanometer to measure blood pressure. There is no relationship between age and hypertension p=0.463 (p>0.05), there is no relationship between stress levels and hypertension p=0.324 (p>0.05), there is a relationship between physical activity and hypertension p=0.023 (p<0.05), and there is no relationship between sleep quality and hypertension p=0.413 (p>0.05). There is no relationship between age, stress level, sleep quality and the incidence of hypertension and there is a relationship between physical activity and the incidence of hypertension.